Sistema remoto de aquisição e monitoramento de variáveis ambientais para aplicações de previsão meteorológica - Menezes, Thiago Pereira de (2012)
Numerous human activities such as agriculture, human supply, civil construction, civil defense and tourism, are strongly linked to climate. Predicting drought, rain and frost leads to a predictive control that prevents financial losses and social. Weather information is of fundamental importance for climate monitoring and weather forecasting. This paper presents the design of hardware and software system for acquisition and tracking of meteorological information. The system consists of a field station, a remote database server and a base station. The field station consists of a microcontroller that collects primary data through analog and digital channels. It manages the use of battery power, performs analog-digital conversion from the sensors, the measurements saved in a local memory bank, encodes and transmits data via the Internet to a data server. The remote database server is a computer connected to the internet that has a database system which receives the data and saved in tables that can be accessed remotely by base stations. Finally, the base station consists of a conventional PC running a free software. The monitoring software provides user-friendly interface, advanced features for managing the equipment, resources to generate graphs and reports and has interaction with social networks (facebook / twitter). Prototypes were developed, one installed at Pici campus of Federal University of Ceará. Correlations and performance tests are used to compare data collected by the prototype with data from a commercial equipment. The system is fully configurable and online monitoring of environmental parameters allows to generate a risk of disaster alerts. There is the possibility of using large-scale system for monitoring and data acquisition at strategic points in the state of Ceará.